Protective effects of reactive functional groups on chondrocytes in photocrosslinkable hydrogel systems. (November 2015) - Bartnikowski, M.; Bartnikowski, N.J.; Woodruff, M.A.; Schrobback, K.; Klein, T.J.
Graphical abstract: Abstract: Photocrosslinkable hydrogels are frequently used in cartilage tissue engineering, with crosslinking systems relying on cytotoxic photoinitiators and ultraviolet (UV) light to form permanent hydrogels. These systems are rarely assessed in terms of optimization of photoinitiator or UV dosage, with non-cytotoxic concentrations from literature deemed sufficient. We hypothesized that the number of reactive functional groups present within a hydrogel polymer is highly relevant when crosslinking, affording cytoprotection to chondrocytes by preferentially interacting with the highly reactive radicals that are formed during UV-mediated activation of a photoinitiator. This was tested using two photocrosslinkable hydrogel systems: gelatin methacrylamide (GelMA) and gellan gum methacrylate (GGMA). We further assessed the effects of two different UV dosages on chondrocyte differentiation while subject to a single photoinitiator dosage in the GGMA system. Most notably, we found that a higher ratio of reactive groups to photoinitiator molecules offers cytoprotective effects, and future developments in photocrosslinkable hydrogel technology may involve assessment of such ratios. In contrast, we found there to be no effect of UV on chondrocyte differentiation at the two chosen dosages. Overall the optimization of photocrosslinkable systems is of great value in cartilage tissue engineering and these data provide a groundwork for such concepts to be developed further. Statement of Significance: Photocrosslinkable hydrogels, which use photoinitiators and predominantly ultraviolet light to form stable matrices for cell encapsulation and tissue development, are promising for cartilage tissue engineering. While both photoinitiators and ultraviolet light can damage cells, these systems have generally not been optimized. We propose that the ratio of reactive functional groups within a polymer to photoinitiator molecules is a critical parameter for optimization of photocrosslinkable hydrogels. Using photocrosslinkable gelatin and gellan gum, we found that a higher ratio of reactive groups to photoinitiator molecules protected chondrocytes, but did not affect chondrocyte differentiation. The principle of cytoprotection by functional groups developed in this work will be of great value in optimizing photocrosslinkable hydrogel systems for cartilage and other tissue engineering applications.